Self-Association of Arrestin Family Members - Chen, Qiuyan (Handb Exp Pharmacol, 2014)
Mammals express four arrestin subtypes, three of which have been shown to self-associate. Cone photoreceptor-specific arrestin-4 is the only one that is a constitutive monomer. Visual arrestin-1 forms tetramers both in crystal and in solution, but the shape of its physiologically relevant solution tetramer is very different from that in the crystal. The biological role of the self-association of arrestin-1, expressed at very high levels in rod and cone photoreceptors, appears to be protective, reducing the concentration of cytotoxic monomers. The two nonvisual arrestin subtypes are highly homologous, and self-association of both is facilitated by IP6, yet they form dramatically different oligomers. Arrestin-2 apparently self-associates into “infinite” chains, very similar to those observed in IP6-soaked crystals, where IP6 connects the concave sides of the N- and C-domains of adjacent protomers. In contrast, arrestin-3 only forms dimers, in which IP6 likely connects the C-domains of two arrestin-3 molecules. Thus, each of the three self-associating arrestins does it in its own way, forming three different types of oligomers. The physiological role of the oligomerization of arrestin-1 and both nonvisual arrestins might be quite different, and in each case it remains to be definitively elucidated.